Lajikkeen, korjuuajan ja -menetelmän vaikutus kevätvehnän itävyyteen ja itämiskypsymättömyyteen - Lallukka, Ulla (Agricultural and Food Science, 1971)
A study was made of the effects of cultivar, harvesting time and harvesting method upon the germinability and the dormancy of spring wheat. It was found that in respect of germinability the spring wheat met the requirements generally placed on good seed provided that the crop was cut at the milk-ripening to full-ripening stage and that the procedure permitted after-ripening before threshing. The germinability of grain harvested at milk-ripeness was very low when the harvesting method did not include after-ripening. There was some decrease in germinability with delay in harvesting. Of the cultivars investigated, Norröna and Svenno seemed most poorly to withstand threshing at the early stage of ripening. When harvested at an over-ripeness stage, the germinability of Norröna declined most sharply. The dormancy of the grain 2—3 weeks after harvesting appeared to be greater in the treatments harvested early than in the treatments harvested at full-ripeness or over-ripeness stages, especially when the harvesting method did not involve after-ripening. Dormancy was greater in the cultivars resistant to sprouting in the ear than in the cultivars susceptible to it. The weather conditions that preceded ripeness also seemed to affect the dormancy of the seed. By sowing time, however, dormancy had declined to such an extent that the germinability of the wheat met the requirements placed on seed.